Editorial: Affective brain-computer interface in emotion artificial intelligence and medical engineering - Lu, Zhaohua; Wang, Tingwen; Zhang, Ruirui (Frontiers in computational neuroscience, 2023)
[...]the system needs to collect blink data of the previous round of subjects in advance, because different subjects have different blink ranges. [...]subsequent work may need to combine more robust algorithms to classify the blinking of different subjects to improve the performance of the system. [...]oxygen-based brain imaging technology, such as functional magnetic resonance imaging (fMRI), has better spatial resolution and has been widely used in neuroimaging research, which is an important tool for researchers to explore the mechanisms of brain activity (Coupeau et al., 2022). To solve this problem, Fei et al. proposed a symmetric end-to-end trainable hybrid convolutional neural network (HC-Net) for the small-sample characteristics of MRI data and the properties of thick-layer scanning. [...]the experimental results of applying the model to task-based patients with schizophrenia suggest that it can be used as a stable biological reference standard for stability and noise immunity.